THE EFFECTIVENESS OF KARELA COMPARED WITH VIJAYASAR IN THE MANAGEMENT OF MADHUMEHA - Om Prakash, Kalouni; Binod Kumar, Singh; D.B, Roka (AYUSHDHARA, 2016)
Vijayasar (Pterocarpus marsupium) has been mentioned in Charak Samhita, as a remedy for Madhumeha (Diabetes Mellitus). A study conducted by ICMR (Indian Council of Medical Research) revealed that the hypoglycemic effects of Vijayasar are comparable to that of tolbutamide. Karela (Mormordica charantia) is another herb used in Madhumeha and it is a routinely used vegetable in Nepal. In this study we measured the effectiveness of Karela in patients of Madhumeha and compared with that of Vijayasar. A total of sixty four patients diagnosed with Madhumeha (Fasting Blood Glucose ≥126mg/dl or Post Prandial Blood Glucose≥200mg/dl) were given either Karela or Vijayasar powder two times a day for one month, along with dietary and lifestyle advices and their blood glucose levels were measured before initiating treatment and after one month of treatment. Changes in the subjective complaints of Madhumeha like Prabhutamutrata, Avilmutrata, etc. and appearance of adverse events were also evaluated. Randomization of treatment was done and dosage was titrated on the basis of glycemic control and duration of Madhumeha. The mean reductions in fasting blood glucose and post prandial blood glucose in Karela treated group are 60.83 mg/dl and 79.74 mg/dl respectively and that in Vijayasar treated. Karela is a safe and effective medicine in the management of Madhumeha and it is as effective as Vijayasar.